Stemflow dynamics of Fuji apple trunk sap in arid oasis area and its response to environmental factors - MA Wentao; CHENG Ping; LI Hong; ZHANG Zhigang; WU Shengli; ZHAO Mingyu (浙江大学学报. 农业与生命科学版)
The aim of this study was to clarify the transpiration water consumption law of apple orchards in the arid oasis area and the driving mechanism of environmental factors on fruit trees, determine the water carrying capacity and formulate an appropriate irrigation system. We continuously monitored the stemflow of Fuji (Changfu 2) apples (Malus domestica Borkh.) in Aksu region of Xinjiang using a stemflow meter with thermal dissipation probe. The results indicated that the diurnal variation of stemflow rate mainly showed a bimodal curve in summer and autumn, and a unimodal curve in spring. The diurnal stemflow was significantly different, and the nighttime stemflow was stable, which mainly concentrated in the time period from sunset to 00:30 on the following day. The nighttime stemflow ratio was September＞May＞August＞July＞June, and the stemflow accounted for 10.28% in September, only 1.06% in June. The stemflow rate was significantly different in different seasons. In summer, the stemflow started early and stopped late, and the stemflow rate was large. Under the instantaneous scale, the stemflow rate was extremely significantly positive correlation with solar radiation, air temperature, water vapor pressure deficit, and wind speed (P＜0.01), and it was extremely significantly negative correlation with relative humidity (P＜0.01). The key factors which affected the instantaneous scale of trunk stemflow rate were solar radiation, air temperature, and water vapor pressure deficit. The daily average stemflow rate was extremely significantly positive correlation with solar radiation, air temperature, water vapor pressure deficit, soil water content, and soil temperature (P＜0.01), and extremely significantly negative correlation with relative humidity (P＜0.01), and it was not related to wind speed (P＞0.05). The key factors affecting the change of stemflow on a daily scale were water vapor pressure deficit and solar radiation. In conclusion, the fruit trees are affected by environmental factors such as solar radiation, water vapor pressure deficit, and soil water content in July in Aksu of Xinjiang, and the orchard consumes a large amount of water by transpiration, so irrigation should be supplemented in time.